Interesses e conflitos de classe na dinâmica da produção do espaço urbano de Arapiraca-AL (2000-2020) - Lima, Rodolfo José Oliveira (2020)
This work aims to discuss some of the urban transformations that Arapiraca, the second largest city in the Alagoas state, distant about 125 km from the capital Maceió, has undergone in the last two decades (2000 - 2020), focusing on the dynamics of social classes in their daily existence. It is intended to demonstrate how the Town Center and the area around Lago da Perucaba, a weir located in the Zélia Barbosa Rocha neighborhood, has been shaped according to the social relations that have been established over the years. Thus, it can be observed how the Town Center has been modified from the desires of the retail capital in constant conflict with the small merchants of the traditional free fairs of the city, during the period that it was held in this neighborhood (tension that culminated in its removal to another location in 2003). This conflict remains today, now with street vendors; workers who maintain in their daily activities a link with the area's past, which has direct implications for the construction of a project of spatial organization that contradicts what the elites desire for this space. The public weir dating from the late 19th century, expanded by the Departamento Nacional de Obras Contra as Secas (DNOCS) in the 1960s, and renamed by Lago da Perucaba in 2009, is located in a historically segregated area that was occupied by low-income people, including fishermen who created a small fishing colony where they live and work for over 50 years. The place has undergone improvements that have made it one of the most valued areas of the city, becoming the target of the interests of real estate capital that has built luxury condominiums, some like a planned community, pressuring the Public Power to force the exit of these residents who live nearby. In this way, it is intended to show how changes in the urban space of Arapiraca are directly linked to the needs and interests of existing social classes, both in the sense of projects intentionally designed by certain sectors, and as an imperative arising from the very way in which social subjects reproduce themselves in the sphere of material relations of production.